Association between preference of pediatric dentistry behavior management technique and parenting styles of parents of children aged 5 to 13 years cared for in a university health center of a private university in Lima, Peru - Cerrón Vásquez, Andrea Milagros (2021)
Aim: To assess the association between preference of pediatric management techniques and parenting styles of parents of children aged 5-13 years cared for in a university health center in Lima, Peru. Materials and methods: The total of the respondents were 160 parents (77 % are female and 78 % belong to the age range of 30 years and over). Parenting styles are assessed using the self-paced questionnaire Parenting Style Dimension Questionnaire (PSDQ). The preference of the behavior management techniques was evaluated by means of an informative sheet of own elaboration where six techniques are included according to the American Academy of Pediatric Dentistry (AAPD) of 2015. As father's age in intervals of years, sex of the father, educational level, number of children, sex of the children, age of the child in years and order of birth of the children. Chi Square and Fisher's Exact Test were analyzed for bivariate analysis and for the numerical variable used Kruskal Wallis. Results: There is no association between preference of behavior management technique and parenting styles. The prevalence of authoritative parenting style and a greater preference for communication techniques were determined, the latter regardless of the parenting style he manages at home. Conclusions: The preference of the behavior management technique is not associated with the parenting styles. However, the prevalence of communication techniques leads us to conclude that more studies should be carried out around it.